Regional review and appraisal of implementation of the Beijing Declaration and Platform for Action and the outcome of the twenty-third special session of the General Assembly (2000) in Latin American and Caribbean countries - Montaño Virreira, Sonia (UN ECLAC CL, 2015)
Presents a context in transformation, the 20 years of changes that the region has experienced. Discusses the economic, political and environmental changes that have transpired and describes the decade of the Beijing Conference and the role of the women's and feminist movement. Covers the progress made in implementing the Beijing Platform for Action over the past two decades and discussess advances in decision-making autonomy. Describes new priorities and challenges associated with the Plan of action. Presents data and conclusions of the report.